PERANCANGAN GEDUNG EXHIBITION MELALUI PENDEKATAN ARSITEKTUR HIGH TECH SEBAGAI PUSAT ISOLASI PASIEN COVID-19 DENGAN MENGGUNAKAN KAMAR PORTABEL - Belfrin Zalukhu; Sri Kurniasih; Dody Kurniawan (MAESTRO, 2022)
The exhibition hall provides space for gatherings such as trade and industry fairs, state conferences, concerts, and even weddings. Bogor Regency is an area is still no place that accommodates larger scale meetings. During the COVID-19 pandemic, Bogor Regency also did not have a place to facilitate the isolation of COVID-19 patients. Seeing these problems, an exhibition building will be designed that can accommodate meeting and exhibition activities with large-scale visitors in Bogor Regency, as well as being used as a health facility for COVID-19 isolation patients during the COVID-19 pandemic. The Exhibition Building in Bogor Regency was designed using a hightech architectural approach. With high tech architecture, it is hoped that this exhibition building can support its function as a center for isolation of COVID-19 patients through the use of modern building elements and technology that will be used to facilitate the activities of isolated patients.